Femoral Varus Osteotomy for Hip Instability after Traumatic Fracture Dislocations of the Hip Associated with Femoral Head Fractures: A Report of Two Cases - Shuichi Miyamoto; Junichi Nakamura; Satoshi Iida; Chiho Suzuki; Seiji Ohtori; Sumihisa Orita; Kazuhisa Takahashi (Case Reports in Orthopedics)
Fracture of the femoral head and the acetabulum with traumatic dislocation of the hip is a severe injury representing various types and unfavorable outcome. We showed a 45-year-old man with Pipkin type-IV fracture and coxa valga. An immediate closed reduction was achieved followed by open reduction and internal fixation via a posterior approach 6 days later. However, dislocation occurred three times without traumatic events after three weeks. CT demonstrated no displacement of posterior fragments or implant failure. Femoral intertrochanteric varus osteotomy was performed to gain concentric stability and successfully resolved recurrent dislocation. Another 45-year-old woman with Pipkin type-IV fracture and coxa valga also underwent closed reduction initially and then continued conservative treatment. After eight weeks, when she started gait training, progressive pain became symptomatic. Persistent hip pain at weight bearing was not improved in spite of arthroscopic synovectomy and osteochondroplasty. Two years after injury, femoral intertrochanteric varus osteotomy was indicated and her refractory pain was resolved gradually. We suggest that femoral varus osteotomy should be considered for superolateral subluxation associated fracture dislocation of the hip in Pipkin type-IV and coxa valga.